Facial Heights as Predictors of Occlusal Vertical Dimension in a Nigerian Population - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Facial height measurements may aid in predicting occlusal vertical dimension (OVD).Aim:To compare facial third measurements among individuals with healthy occlusions for a predictive ratio for occlusal vertical dimension determination.Setting and Design:A cross-sectional prospective observational study at the Dental Clinic of Aminu Kano Teaching Hospital. Sampling was purposive.Materials and Methods:A digital caliper was used to measure the upper facial height (UFH), the midfacial height (MFH), and the lower facial height (LFH) of 103 participants.Statistical Analysis Used:The data collected were analyzed with IBM Statistical Package for the Social Sciences (SPSS) version 25. The level of statistical significance was set atP≤ 0.05.Results:There were 69 male (67%) and 34 female (33%) members in the cohort analyzed. The ages of the participants ranged from 18 to 58 years, with a mean age of 27.3 ± 6.8 years. The UFH ranged from 60 to 110 mm with a mean value of 82.2 ± 9.8 mm. The MFH ranged from 55 to 100 mm with mean value of 74.6 ± 9.9 mm. The LFH ranged from 60 to 90 mm with a mean of 73.2 ± 7.4 mm. There was a significantly positive correlation between UFH and LFH (r= 0.22). This was similar to that of MFH and LFH (r= 0.61). The best fit model equation for the prediction of LFH was found to be LFH = 31.495 + (0.442 × MFH).Conclusions:This study found MFH to be a predictable factor for LFH estimation which can be used for OVD determination.